Nano-Safety : What We Need to Know to Protect Workers - Aquino, Grace V.; Asmatulu, Eylem; Asmatulu, Ramazan; Fazarro, Dominick; Foster, Barbara; Hanks, Craig; Hernandez, Roger A.; Hirt, Evelyn H.; Kay Hanks, Emily; Khan, W. S.; Newberry, Deb.; Sayes, Christie; et al. (Berlin ; Boston : De Gruyter, 2017)
Nanotechnology safety is the practice of handling engineered nanomaterials in production and manufacturing. Good practice consists of understanding and interpreting Material Safety Data Sheets, behaving safely when working with yet unknown nanomaterials, understanding health effects, and proactively creating safety measures against potential hazards. This book introduces nanotechnology risk management to readers from academia and industry.
Frontmatter -- Foreword / Geraci, Charles -- Preface / Trybula, Walt -- Contents -- About the Editors -- List of Contributing Authors -- 1. The World of Nanotechnology / Foster, Barbara -- 2. The World of Engineering Nanomaterials / Asmatulu, Eylem -- 3. The Importance of Safety for Manufacturing Nanomaterials / Khan, W.S. / Asmatulu, R. -- 4. Safety Approaches to Handling Engineered Nanomaterials / Tate, Jitendra S. / Hernandez, Roger A. -- 5. Certification: Validating Workers' Competence in Nano-safety / Sayes, Christie M. -- 6. Understanding the Implications of Nanomaterial Unknowns / Trybula, Walt / Newberry, Deb -- 7. What Is Considered Reliable Information? / Hirt, Evelyn H. / Trybula, Walt -- 8. Ethics and Communication: The Essence of Human Behavior / Hanks, J. Craig / Hanks, Emily Kay -- 9. Behavior-Based Worker Safety for Engineered Nanomaterials / Sayes, Christie M. / Burkleo, Patrick Van / Aquino, Grace V. -- 10. The Future of Nanotechnology Safety / Fazarro, Dominick -- Index.
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 26. Sep 2017).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Nanotechnology -- Safety measures; Nanotechnology -- Safety regulations; Nanotechnologie -- Sécurité -- Mesures; Nanotechnologie -- Sécurité -- Règlements.; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Nanotechnology; Electronic books; Safety regulations